2016
DOI: 10.1017/s0021859616000940
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of polymorphisms in mysostatin gene and their allele substitution effects showed weak association with growth traits in Iranian Markhoz goats

Abstract: SUMMARYPolymorphisms in the myostatin (MSTN) gene were detected in 150 female Iranian Markhoz goats. Two 573 base pairs (bp) and 475 bp fragments of the MSTN gene, which contains a deletion 5 bp indel (206 TTTTA/), in the region of exon 1 encoding the 5′ untranslated region (UTR) of the MSTN transcript, and two single-nucleotide polymorphisms (SNPs) of substitution (339T/A, 169T/G) in exon 1 and 3 regions, respectively, were amplified. The polymerase chain reaction (PCR) products were digested separately using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Numerous studies and researches reported that there were various SNPs and indels loci in both domestic and exotic commercial breeds of goat, sheep, cattle, pig, rabbit, as well as poultry [36]. Additionally, plenty of research focused on a 5 bp indel in 5' UTR of MSTN gene within different goat breeds to uncover its distributions and effects on growth traits of goats [37]. A research detected distributions of the 5 bp indel in Black Bengal, Sirohi, Osmanabadi, Jakhrana, Jamunapari, Barbari, Marwari goat breeds [38].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies and researches reported that there were various SNPs and indels loci in both domestic and exotic commercial breeds of goat, sheep, cattle, pig, rabbit, as well as poultry [36]. Additionally, plenty of research focused on a 5 bp indel in 5' UTR of MSTN gene within different goat breeds to uncover its distributions and effects on growth traits of goats [37]. A research detected distributions of the 5 bp indel in Black Bengal, Sirohi, Osmanabadi, Jakhrana, Jamunapari, Barbari, Marwari goat breeds [38].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated weight of loin primal cuts, chum and hind leg were observed increased significantly[18]. Other previous studies reported three mutations on position number 224bp, 226bp and 242bp in MSTN exon 1 of makuei sheep that were found responsible for increase heart girth and leg circumference[19]…”
mentioning
confidence: 76%
“…However, both genotypes (wild-type and deletion genotype) were found in TS, LXBH, STHS, and LFTS sheep. This difference might be due to differences in breeding, including differences in geographic locations of breeds and various environmental factors [ 24 ], or perhaps, the number of individuals with heterozygous deletion genotypes was too small to detect in HS, SS, and AUW sheep. In previous studies, nontarget products were heteroduplexes [ 25 ], and heteroduplexes were only in individuals heterozygous for the mutation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%